Problems and Solutions to Cybersecurity. - Mengniyazov Quvondiq Jumanazar o'g'li (Zien Journals, 2022)
This article provides general insights into cybersecurity, its problems, and its solutions
Keywords: Cybersecurity; CSEC2017; testing; information